The Parent-Child Relationship and Child Development in the Context of Historical and Complex Traumas : Perceptions of the Inuit Community of Kangiqsualujjuaq - Dugas, Pascale; Asselin, Antoine; Poulin-Latulippe, David; Etok, Nancy; Annanack, Elassie; Terradas, Miguel (Études Inuit Studies, 2024)
In the community of Kangiqsualujjuaq, as elsewhere in Nunavik, the socioeconomic conditions in which Inuit families live are much more difficult than those in the rest of Canada. These conditions are a symptom of a colonial past that has resulted in many historical and complex traumas. In a traumatic context, mentalization capacity, which refers to the ability to interpret one’s own behaviours and those of others in terms of underlying mental states, can have a protective effect on the individual. The present exploratory action research aimed to document the perceptions of members of this Inuit community regarding the particularities of the parent-child relationship. Two focus groups were conducted with community members, counsellors, and elders. A thematic analysis was done from the collected verbatims and guided by a phenomenological perspective. Factors extracted from the results were associated with well-being and suffering in the parent-child relationship and placed on a continuum. Openness and transmission were associated with well-being, while closure and a breakdown in communication were linked to suffering. Finally, this study highlights the relevance of focusing on mentalization among Inuit.